2001
DOI: 10.1152/ajprenal.2001.280.3.f365
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-induced cardiorenal protection: potential cellular, biochemical, and molecular mechanisms

Abstract: A number of cellular and biochemical processes are involved in the pathophysiology of glomerular and vascular remodeling, leading to renal and vascular disorders, respectively. Although estradiol protects the renal and cardiovascular systems, the mechanisms involved remain unclear. In this review we provide a discussion of the cellular, biochemical, and molecular mechanisms by which estradiol may exert protective effects on the kidneys and vascular wall. In this regard, we consider the possible role of genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
213
1
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(226 citation statements)
references
References 303 publications
(397 reference statements)
3
213
1
9
Order By: Relevance
“…24 We demonstrated that the beneficial effect of ARB to improve vascular remodeling is caused by not only blockade of the AT 1 receptor but also stimulation of the unmasked AT 2 receptor by Ang II. 16 Therefore, it is possible that the effect of ARB is linked to the stimulation of AT 2 receptor-mediated signaling such as activation of protein tyrosine phosphatases, 25 which is further potentiated by estrogen.…”
Section: Liu Et Al Effect Of Estrogen and Arb On Vascular Remodeling 455mentioning
confidence: 83%
“…24 We demonstrated that the beneficial effect of ARB to improve vascular remodeling is caused by not only blockade of the AT 1 receptor but also stimulation of the unmasked AT 2 receptor by Ang II. 16 Therefore, it is possible that the effect of ARB is linked to the stimulation of AT 2 receptor-mediated signaling such as activation of protein tyrosine phosphatases, 25 which is further potentiated by estrogen.…”
Section: Liu Et Al Effect Of Estrogen and Arb On Vascular Remodeling 455mentioning
confidence: 83%
“…27 In animals and isolated cells, estrogen induces multiple effects that in theory should reduce CHD risk. 27 For example, estrogen upregulates the synthesis of vasodilatory and growth inhibitory molecules such as nitric oxide, prostacyclin, cAMP, and adenosine.…”
Section: Experimental Studies In Animals and Isolated Cells Suggest Tmentioning
confidence: 99%
“…27 In animals and isolated cells, estrogen induces multiple effects that in theory should reduce CHD risk. 27 For example, estrogen upregulates the synthesis of vasodilatory and growth inhibitory molecules such as nitric oxide, prostacyclin, cAMP, and adenosine. Also, estrogen downregulates the synthesis of vasoconstrictor molecules, growth inducers, and atherosclerosis inducers, such as endothelin, homocysteine, angiotensin II, renin activity, angiotensin-converting enzyme activity, catecholamines, and low-density lipoprotein.…”
Section: Experimental Studies In Animals and Isolated Cells Suggest Tmentioning
confidence: 99%
See 2 more Smart Citations